Lab manual to accompany health assessment in nursing. - Weber, Janet; Kelly, Jane H.; Sprengel, Ann (New York, United States : Wolter Kluwer / Lippincott Williams & Wilkins, 2010)
An introductory level health assessment text for RN-level students. It presumes no prior knowledge of health assessment
NUR
Keywords: Nursing assessment -- Problems and exercises; Nursing assessment -- Methods -- Problems and exercises